The impact of urban light rail transit on double-story terraced property values in the Greater Kuala Lumpur, Malaysia - Mohd Faris Dziauddin (Indonesian Journal of Geography, 2021)
Introducing a rail transit system into an urban region is expected to increase land values, and subsequently, residential property values. Despite this general belief, there has been limited research on the impact of proximity to urban light rail transit stations in developing countries setting. This study, therefore, investigates the impact of proximity to urban light rail transit on double-story terraced property values in the Greater Kuala Lumpur, Malaysia, using hedonic pricing model. The findings suggest urban light rail transit has a positive and significant impact on surrounding double-story terraced residential property values – estimated at a premium of 12.3% and 9.8% for properties located up to 1000 m and 1001 – 2000 m to the nearest light rail transit station respectively. The findings of the study are useful for investors and developers, namely to build more houses near urban rail transit infrastructure since they lead to significant appreciation in value.